Symbiosis okcydental and oriental greek-catholic group as a identity of the UGCC - M. Kobryn (Українське Pелігієзнавство, 2014)
In the article Kobryn Mykhaylo «Symbiosis okcydental and oriental greek-catholic group as a identity of the UGCC» has been investigated the evolution of Okcydental and Oriental identity groups within the Ukrainian Greek Catholic Church. The concept of «religious identity» has been determined. The interaction and relationship of Okcydental and Oriental Greek- Catholic groups has been analyzed. The method of combining pro-Western and pro-Eastern identity groups in the creation of a common identity of the Ukrainian Greek-Catholic Church has been considered.